Elucidating the large variation in ion diffusivity of microelectronic packaging materials. (September 2022) - Herrmann, A.; van Soestbergen, M.; Erich, S.J.F.; van der Ven, L.G.J.; Huinink, H.P.; van Driel, W.D.; Mavinkurve, A.; De Buyl, F.; Adan, O.C.G.
Abstract: The risk of corrosion poses a challenge to meet the stringent reliability requirements of microelectronic devices that are used in harsh environments. Microelectronic devices are often encapsulated in polymer packaging materials, which protect them from corrosion. These polymers are, however, not completely hermetic and thus allow small amounts of ions and moisture to reach the device, which might cause corrosion of the microelectronic circuitry. To improve and predict the reliability of the device, it is important to quantify the ion diffusivity in these materials. Previously reported values for the ion diffusivity vary by multiple orders of magnitude for a single class of material. Here, we investigate the causes for this discrepancy using three experimental methods: (i) saltwater immersion, (ii) diffusion cell measurements, and (iii) transient electric current measurements. Several materials, such as silicone, epoxy, and polyamide, were tested to cover the broad spectrum of polymers used by the microelectronics industry. We found that the discrepancies are likely due to the strong dependence of the ion diffusivity on both the moisture content within the polymers, as well as on the salt concentration and pH of the solutes. Furthermore, we found that the very low ion diffusivity causes long measuring times, and thus a large risk for errors from contamination, leakage, or minor defects in the samples. Highlights: Reported ion diffusivities in molding compounds vary by orders of magnitude. Three methods and several materials were used to study the causes of this variation. Experimental conditions (e.g. temperature, pH, moisture) largely affect diffusion. H + was found to replace Mn 2+ as cation to increase diffusion of Cl − in polyamide. Ion diffusivity in epoxy resin above glass transition follows an Arrhenius relation.